Стан ендокринної функції тимуса у дітей групи ризику у передклінічний період розвитку цукрового діабету 1-го типу - Замотаєва, Г. А. (Clinical Endocrinology and Endocrine Surgery, 2010)
The authors present the results of a study of blood levels of thymulin (a hormone that is secreted by thymic epithelial cells) in 69 normoglycemic children being at increased risk of type 1 diabetes mellitus development (offsprings of first line kin and sibs of diabetes mellitus patients), and in 18 children with newly diagnosed diabetes before insulin therapy initiation. The control group consisted of 39 practically healthy children without a family history of diabetes mellitus. In 38 children from the risk group, antibodies to antigens of pancreatic beta cells (GAD, IA-2, IAA) were identified; in the rest of children from this group (31 children) autoantibodies (AAB) were not revealed in the blood. It has been established that in children from the risk group with a positive response to AAB, thymulin content was by 1.5 times (р<0.001) lower compared with control values. The most significant decrease in thymulin secretion was observed on the eve of diabetes manifestation. The data obtained suggest the presence of thymic functional abnormalities in children with autoimmune process in the pancreas. A decrease in thymulin blood levels was noted in the period preceding the development of clinical phase of the disease. Thymulin level assay in children with a family history of diabetes may be used as an additional criterion for assessment of the likelihood of type 1 diabetes mellitus development.